Chemotherapy induced nausea and vomiting may cause anxiety and depression in the family caregivers of patients with cancer - Luo, Xiaozhen; Yang, Lili; Chen, Jing; Zhang, Jing; Zhao, Quanqing; Zhu, Jiang (Frontiers in Psychiatry, 2023)
Objective To investigate the impact of chemotherapy induced nausea and vomiting (CINV) on the anxiety and depression of the primary family caregivers of patients with cancer. Methods This study screened family caregivers of patients with cancer undergoing highly emetogenic chemotherapy (HEC) containing a 3-day cisplatin regime. Caregivers who did not experience anxiety or depression at baseline screening were enrolled in this study. Based on the patients’ CINV status during chemotherapy, their family caregivers were divided into two groups: patients who experienced CINV (CINV group) and patients who did not experience CINV (No-CINV group). All enrolled family caregivers completed the Hospital Anxiety and Depression Scale (HADS) questionnaire on the fourth and 8 days of chemotherapy. Results A total of 256 family caregivers were screened for this study, of which 195 caregivers without anxiety or depression at baseline were included. A total of 150 (76.9%) patients undergoing chemotherapy experienced acute CINV; 63 (42%) of their family caregivers experienced anxiety, and 65 (43.3%) developed depression. This was significantly higher than the experiences of the No-CINV group (2.2%, P < 0.001; 0%, P < 0.001, respectively). Among the patients undergoing chemotherapy, 86 (44.1%) experienced delayed CINV. The incidence of anxiety and depression in the family caregivers of patients with delayed CINV were 27.9 and 36%, respectively, both of which were significantly higher than that in the family caregivers of the No-CINV group (0.9%, P < 0.001; and 0.9%, P < 0.001, respectively). Conclusion Acute and delayed CINV occurring in patients during chemotherapy may induce anxiety and depression in their family caregivers.